ANALISIS PENERAPAN PEMBIAYAAN GADAI EMAS SYARIAH (GES) DALAM PERSPEKTIF FIQH MUAMALAH DI BMT UGT NUSANTARA CAPEM MUNCAR KABUPATEN BANYUWANGI - Feryansyah Prima Ernanda; Nur Anim Jauhariyah; Ahmad Munib Syafa'at; Muhammad Riza Aziziy (Jurnal Istiqro, 2022)
The objectives of this research are 1) To know the application of the qardh principle to the Sharia Gold Pawn product at BMT UGT Nusantara Capem Muncar. 2) Knowing the application of the principle of rahn on Sharia Gold Pawn products in BMT UGT Nusantara Capem Muncar. 3) to find out the application of the principle of ijarah to Sharia Gold Pawn product at BMT UGT Nusantara Capem Muncar. The research approach uses qualitative methods phenomenology with data collection methods with in-depth interviews and documentation to employees of BMT UGT Nusantara Capem Muncar. The results of the study show that the qardh principle in the Islamic Pawn Gold product is used to bind loans given by BMT to customers. The rahn principle is used to bind the collateral in the form of gold and the ijarah principle is used to bind the rental of the place for storage and security of the collateral goods. The conclusion from the analysis of the application of the contract in the practice of Islamic gold pawning (GES) at BMT UGT Nusantara Capem Muncar, shows that the principle of ijarah on sharia gold pawn products at BMT UGT Nusantara Capem Muncar is used as a contract to bind the rental of storage and security of collateral goods, the determination of fees or ujrah on this product is not in accordance with sharia provisions as described in the regulations governing ujrah and Bank Indonesia Circular Letter regarding gold-backed qardh.